P-002 YI First Dose IgE-Mediated Allergy to Infliximab Due to Galactose-α-1, 3-Galactose Allergy. (March 2016) - Stein, Daniel; Schuyler, Alex; Commins, Scott; Behm, Brian; Chitnavis, Maithili
Abstract : Background: Mammalian meat allergy is an IgE antibody-mediated response to a mammalian oligosaccharide epitope galactose-α-1, 3-galactose (alpha-gal). Anaphylaxis may occur after patients bitten by a lone star tick develop IgE antibodies to alpha-gal and are re-exposed to the same epitope following ingestion of mammalian products such as beef, pork, and lamb. Severe anaphylaxis to monoclonal antibodies glycosylated with alpha-gal (i.e., cetuximab) has been reported in this patient population. We present a case of first dose IgE-mediated allergic reaction to infliximab in a woman with mammalian meat allergy. A 53-year-old woman with a history of Crohn's disease was initiated on infliximab. She developed diffuse urticaria and wheezing during the first infusion, indicative of a pre-formed IgE response. She was pre-treated with corticosteroids and diphenhydramine for a second treatment, but developed a similar reaction and therapy was discontinued. Subsequent therapy with vedolizumab was initiated without recurrence of symptoms. Separately, she was confirmed to have mammalian meat allergy mediated by IgE antibody to galactose-α-1, 3-galactose. Methods: Patient serum was collected and compared to serum from 3 other individuals with known mammalian meat allergy (mediated by IgE to galactose-α-1, 3-galactose) and 2 controls. Total and specific IgE antibodies to monoclonal antibodies derived from cell lines that glycosylate with galactose-α-1, 3-galactose (cetuximab, infliximab, and natalizumab) as well as non-glycosylated monoclonal antibodies (rituximab and vedolizumab) were measured with the use of either ImmunoCAP (Phadia U.S.) or a modified assay with streptavidin-coated ImmunoCAP. Each monoclonal Ab was biotinylated, and approximately 5 μg was added to each streptavidin-coated ImmunoCAP before serum was added. The assays were performed with the ImmunoCAP250 instrument. The threshold value for a positive reaction was 0.35 IU per milliliter. Results: Positive reactions were seen with monoclonal antibodies from cell lines that glycosylate with galactose-α-1, 3-galactose (infliximab, natalizumab, and cetuximab) in our patient and the 3 individuals with known galactose-α-1, 3-galactose allergy, but not in the 2 controls. No reaction was seen to the non-glycosylated monoclonal antibodies (rituximab or vedolizumab) in any of the samples. Conclusions: First-dose allergic reactions to infliximab are rare. We describe evidence for a potential allergic mechanism through IgE-mediated reaction to galactose-α-1, 3-galactose. Immediate anaphylaxis has previously been described in patients with first exposure to intravenous cetuximab, in which galactose-α-1, 3-galactose is present on the FAb portion of the heavy chain, but similar reactions to infliximab have not previously been described to our knowledge. Care should be taken in patients with known mammalian meat allergy prior to use of infliximab.